Human respiratory syncytial virus in children hospitalized for acute lower respiratory infection - Salomão Junior, João Batista; Gardinassi, Luiz G. A. [UNESP]; Simas, Paulo V. M. [UNESP]; Bittar, Cintia O. [UNESP]; Souza, Fátima Pereira de [UNESP]; Rahal, Paula [UNESP]; Zanetta, Dirce M. T. (Sociedade Brasileira de Pediatria, 2011)
Objective: To evaluate the prevalence and seasonality of human respiratory syncytial virus (HRSV) in children aged 0 to 6 years, hospitalized with acute lower respiratory infection (ALRI) in Sao Jose do Rio Preto, SP, Brazil, and the association between age, diagnosis, and HRSV.Methods: Between May 2004 and September 2005, we studied 290 consecutive episodes of community-acquired ALRI in children aged 0 to 6 years admitted to the Hospital de Base of Sao Jose do Rio Preto. In order to detect HRSV, nasopharyngeal secretion samples were collected and RT-PCR molecular analysis was performed.Results: The HRSV prevalence was 29.3% for the cases of hospitalized patients with ALRI. ALRI was common in infants (median age = 13.5 months). HRSV was more frequent in cases of bronchiolitis (64%) and during the first year of life (35%). Episodes of HRSV infection occurred between fall and spring, showing higher frequency in 2004 than in 2005. Clinical and radiological criteria were not sufficient to establish the diagnosis of infection with HRSV. Antibiotic therapy was used in 78.8% of episodes of HRSV.Conclusions: There was a high prevalence of HRSV in children aged 0 to 6 years who were hospitalized for ALRI, predominantly in younger patients or those with bronchiolitis. The circulation of the virus varied in the two years studied. Our results suggest the need for laboratory diagnosis of HRSV in the clinical practice.

OBJETIVO: Avaliar a prevalência e a sazonalidade do vírus respiratório sincicial humano (VRSH) em crianças de 0 a 6 anos hospitalizadas por infecção aguda das vias aéreas inferiores (IVAI) em São José do Rio Preto (SP) e a associação entre faixa etária, diagnóstico e VRSH. MÉTODOS: Entre maio de 2004 e setembro de 2005, foram estudados 290 episódios consecutivos de IVAI adquiridos na comunidade em crianças de 0 a 6 anos internadas no Hospital de Base de São José do Rio Preto. Para identificação do VRSH, foram coletadas amostras de secreção de nasofaringe e realizou-se análise molecular por meio da técnica de RT-PCR. RESULTADOS: A prevalência de VRSH foi de 29,3% nos episódios de IVAI hospitalizados. A IVAI foi frequente em lactentes (mediana de idade = 13,5 meses). O VRSH foi mais frequente nos casos de bronquiolite (64%) e no primeiro ano de vida (35%). Os episódios de infecção por VRSH ocorreram entre o outono e a primavera, com frequência maior em 2004 do que em 2005. Os critérios clínicos e radiológicos não foram suficientes para o diagnóstico de infecção pelo VRSH. Em 78,8% dos episódios de VRSH, houve tratamento com antibiótico. CONCLUSÕES: A prevalência do VRSH em crianças de 0 a 6 anos hospitalizadas por IVAI foi elevada, com predomínio nas mais jovens ou com bronquiolite. A circulação do vírus variou nos dois anos estudados. Os resultados sugerem necessidade de diagnóstico laboratorial do VRSR na prática clínica.
Keywords: Respiratory infections; human respiratory syncytial virus; hospitalized children; bronchiolitis